2019
DOI: 10.1002/ncp.10316
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Risk in Hospitalized Pediatric Patients: Higher Complication Rate and Higher Costs Related to Malnutrition

Abstract: Background Hospitalized children present higher rates of undernutrition. Malnutrition can lead to a more complex hospitalization process with an increased length of stay and higher costs. Our aim was to analyze nutrition risk in hospitalized children and its relationship with clinical outcomes in a tertiary level hospital. Methods This is a single institution prospective observational study. The research involved 282 consecutive children admitted along 3 months. Anthropometric measurements and nutrition risk b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…Vulnerability to infectious pathogens is associated with malnutrition-related deficiencies in function of both innate and adaptive immune systems [18,39]. Studies also found that hospitalized pediatric patients have greater complication rates and higher costs when they are malnourished [40]. Further, a recent study examined people who had been picky eaters in childhood with mildly or transiently impaired growth; as young adults, they had lower intake of fruit, vegetables, and whole grains and more frequent intake of snack foods, sugar-sweetened beverages, and high-fat fast-foods, thus setting themselves up for poor health outcomes later in life [41].…”
Section: Other Studies On Picky Eating Behaviors and Growth/health Impairment In Young Childrenmentioning
confidence: 99%
“…Vulnerability to infectious pathogens is associated with malnutrition-related deficiencies in function of both innate and adaptive immune systems [18,39]. Studies also found that hospitalized pediatric patients have greater complication rates and higher costs when they are malnourished [40]. Further, a recent study examined people who had been picky eaters in childhood with mildly or transiently impaired growth; as young adults, they had lower intake of fruit, vegetables, and whole grains and more frequent intake of snack foods, sugar-sweetened beverages, and high-fat fast-foods, thus setting themselves up for poor health outcomes later in life [41].…”
Section: Other Studies On Picky Eating Behaviors and Growth/health Impairment In Young Childrenmentioning
confidence: 99%
“…13 Another study also mentioned that children with HaM will have approximately 9 days of hospital stay. 14 This study showed that the results of sensitivity and specificity values of STRONGkids were better than Alarm Malnutrition. It indicated that STRONGkids was considered as a good screening tool in detecting the risks for HaM.…”
Section: Discussionmentioning
confidence: 68%
“…Higher malnutrition risk is associated with growth impairment, longer LOS, increased hospital costs, and higher mortality ( 28 ). Although few studies have directly confirmed the relationship between malnutrition risk and PICU readmission in adults or children, it has been confirmed that higher malnutrition risk is associated with the occurrence of malnutrition and malnutrition will cause readmission ( 29 ). In recent studies of different nutrition screening tools in pediatrics, StrongKids was considered a method of evaluating good clinical performance ( 30 ).…”
Section: Discussionmentioning
confidence: 99%